Fully Endoscopic Minimally Invasive Transrectus Capitis Posterior Muscle Triangle Approach to the Posterolateral Condyle and Jugular Tubercle - Mingdong, Wang; Fernandez-Miranda, Juan C.; Mathias, Roger Neves; Wang, Eric; Gardner, Paul; Wang, Hong (Journal of Neurological Surgery Part B: Skull Base, 2017)
Background We evaluated a transrectus capitis posterior muscle triangle approach to the posterolateral foramen magnum, occipital condyles, jugular tubercle, and the fourth ventricle. We also assessed factors that affect the amount of bone removal required.Objective To evaluate if the proposed approach is as effective as standard open approaches to expose the lateral portion of the foramen magnum.Methods The proposed minimally invasive fully endoscopic approach was performed in 15 cadaveric specimens using 4-mm (0- and 45-degree) endoscopes.Results Using a 5-cm straight paramedian incision, the rectus capitis posterior minor and major muscles were partially removed unilaterally, providing a corridor through the muscles to reach the foramen magnum region. After meticulous soft tissue dissection, key anatomical landmarks can be identified such as the greater occipital nerve, the vertebral artery that wraps around the atlanto-occipital joint, and the bony protuberance that heralds the occipital condyle. A suboccipital craniotomy associated with the transcondylar, supracondylar or paracondylar approach is performed depending on the amount of bone removal desired to maximize the surgical view. By doing so, the jugular foramen can be exposed laterally as well as the fourth ventricle medially.Conclusion The proposed endoscopic approach can provide access through the transrectus capitis posterior muscle triangle leading directly to the occipital condyle. A stepwise approach is critical to gain a surgical corridor to the inferolateral petroclival region and the fourth ventricle.
Keywords: posterolateral condyle; jugular tubercle; minimally invasive; transrectus capitis posterior muscle triangle; fully endoscopic